LPG Concentration Measurement in Vehicles Transporting Dangerous Goods - Vestenicky, Martin; Vestenicky, Peter (Communications - Scientific letters of the University of Zilina, 2011)
This paper describes the design of intelligent sensor unit for LPG (Liquefied Petroleum Gas) concentration measurement in the air. The sensor unit is a part of sensor network which has been designed for vehicles transporting dangerous goods. The described sensor unit uses sensor element based on SnO2 structure which is vapoured on the aluminum substrate. Main part of the paper is focused on hardware solution of the sensor unit, signal processing applied on signal from its sensor element, compensation of air temperature and relative humidity influence on the sensor resistance and description of its application layer communication protocol.